SSRI Use During Pregnancy and Risk for Postpartum Hemorrhage: A National Register-based Cohort Study in Sweden. Issue 3 (September 2021) - Skalkidou, A.; Sundstrom-Poromaa, I.; Wikman, A.; Hesselman, S.; Wikstrom, A.K.; Elenisa, E.
Abstract : ( BJOG . 2020;127:1366–1373) Up to 1 in 6 women globally are affected by maternal mood disorders and perinatal depression, and over the course of the last 20 years, treatment with selective serotonin reuptake inhibitors (SSRIs) has dramatically increased. SSRIs remain the drug of choice for depression affecting pregnant women despite the small elevated risk of persistent pulmonary hypertension of the newborn, cardiovascular defects, and need for neonatal intensive care. However, as the use of SSRIs in nonpregnant populations is associated with elevated risk for upper gastrointestinal tract bleeding, intracranial hemorrhage, and increased postoperative blood loss, this study's primary aim was to investigate whether or not SSRIs used by pregnant women lead to a higher risk of postpartum hemorrhage (PPH). The hypothesis was that use of SSRIs in pregnancy would increase the risk of PPH in women with low-risk pregnancies in Sweden.